2003
DOI: 10.1021/es020137k
|View full text |Cite
|
Sign up to set email alerts
|

Factors Governing the Atmospheric Deposition of Polycyclic Aromatic Hydrocarbons to Remote Areas

Abstract: Polycyclic aromatic hydrocarbons (PAH) were measured in bulk atmospheric deposition collected in three remote areas of Europe during 1997-1998. Mean total PAH fluxes over a period of 18 months were 1560 +/- 750 and 1150 +/- 630 ng m(-2) mo(-1) in the Pyrenees and the Alps, respectively. In the Caledonian mountains (Scandinavia) the observed mean fluxes were 1900 +/- 940 ng m(-2) mo(-1) (6 month collection). Similar qualitative PAH compositions (p values <0.05) in the bulk atmospheric deposition have been obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
45
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(48 citation statements)
references
References 32 publications
3
45
0
Order By: Relevance
“…Deposited PAHs may re-volatilize, be transported over long distances and be deposited again on soil and water surfaces far from the emission sources (Fernández et al, 2003), e.g.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Deposited PAHs may re-volatilize, be transported over long distances and be deposited again on soil and water surfaces far from the emission sources (Fernández et al, 2003), e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Only in a few cases has deposition been considered in remote areas such as high altitude regions (Fernández et al, 2003;Offenthaler et al, 2009;Foan et al, 2012). However, high mountain areas provide the reference background information of the pollution impact, in this case PAHs, of the overall anthropogenic activities in large regions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is evidence that even these areas receive impacts of long-range atmospheric transported pollutants such as POPs (Blais et al, 1998;Wang et al, 2009;Estellano et al, 2008;Fernández and Grimalt, 2003;Fernández et al, 1999;Daly and Wania, 2005). As observed in the polar regions (Cabrerizo et al, 2012;Halsall, 2004), field studies in Europe , western Canada (Davidson et al, 2003), South America (Grimalt et al, 2004a;Pozo et al, 2007) and the Tibetan Plateau among others, have shown that mountains can act as cold-traps for POPs or even organic compounds with limited atmospheric transport, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Atmospheric deposition is the main pathway by which POPs are incorporated into pristine regions (Carrera et al, 2002;Fernández et al, 2003). Unfortunately, there are substantial gaps of knowledge concerning the specific transfer mechanisms occurring at these sites, such as the influence of the physical-chemical properties of the trapped compounds and the environmental factors that are relevant for the overall deposition efficiencies.…”
Section: Introductionmentioning
confidence: 99%